Molybdenum‐Based Nanomaterials for Photothermal Cancer Therapy. Issue 11 (9th October 2022) - Zhou, Zhan; Li, Xiangqian; Hu, Tingting; Xue, Baoli; Chen, Hong; Ma, Lufang; Liang, Ruizheng; Tan, Chaoliang
Abstract : Molybdenum (Mo) is a trace dietary element that is essential for human survival. Several molybdenum‐containing enzymes (e.g., aldehyde oxidase, xanthine oxidase and sulfite oxidase) are associated with key metabolic activities in the body. Molybdenum‐based nanomaterials (Mo‐NMs), including molybdenum dichalcogenides, molybdenum oxides, molybdenum‐based polyoxometalates, and molybdenum‐based nanocomposites, have been extensively explored in biomedical applications including photothermal therapy (PTT) because of their unique chemical and physical properties as well as excellent biocompatibility and biodegradability. PTT, which relies on converting the near‐infrared (NIR) light energy into thermal energy to achieve therapeutic effects, has attracted considerable attention in past decades for cancer treatment because of its localized and trigger‐activated therapeutic effects. In this review, the state‐of‐the‐art progress on Mo‐NMs for photothermal cancer treatment is summarized. The classification, synthesis, and surface functionalization of Mo‐NMs are first introduced. Then the discussion of PTT and PTT‐combined therapies of Mo‐NMs for effective cancer treatment is focused on. Following that, the toxicity assessment of Mo‐NMs is also discussed. Finally, a short discussion on the challenges and future prospects in this field is presented. Abstract : This review summarizes the state‐of‐the‐art progress on molybdenum‐based nanomaterials (Mo‐NMs) for photothermal cancer treatment. The classification, synthesis, and surface functionalization of Mo‐NMs are first introduced. Then the discussion of photothermal therapy (PTT) and PTT‐combined therapies of Mo‐NMs for effective cancer treatment is focused on. Finally, a short discussion on the challenges and future prospects in this field is presented.